2004
DOI: 10.1021/jo049774e
|View full text |Cite
|
Sign up to set email alerts
|

Study of a New Rate Increasing “Base Effect” in the Palladium-Catalyzed Amination of Aryl Iodides

Abstract: Evidence for an interphase deprotonation of Pd(II)-amine complexes with weak carbonate base has been gained for the first time. When a rate-limiting deprotonation step is involved in the catalytic cycle, controlling the structure (shape and size of the particles) and/or molar excess of the carbonate base used can significantly increase the reaction rate of Buchwald-Hartwig aminations. By taking such a "base effect" into account a general protocol for the intermolecular amination of aryl iodides with all types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 21 publications
3
79
0
Order By: Relevance
“…In non-polar solvents such as toluene, in which these inorganic bases have very low solubility, the deprotonation of the Pd-bound amine is thought to occur at the solid-liquid boundary. 149 In this situation, the particle size and shape of the inorganic base can be important in determining the rate and ultimate success of a cross-coupling reaction. 150, 151 This topic has seen the most detailed discussion by Maes in the use of Cs 2 CO 3 in Pd-catalyzed amination with BINAP as ligand, 149 although the findings are almost certainly applicable to biaryl phosphine ligands.…”
Section: Key Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-polar solvents such as toluene, in which these inorganic bases have very low solubility, the deprotonation of the Pd-bound amine is thought to occur at the solid-liquid boundary. 149 In this situation, the particle size and shape of the inorganic base can be important in determining the rate and ultimate success of a cross-coupling reaction. 150, 151 This topic has seen the most detailed discussion by Maes in the use of Cs 2 CO 3 in Pd-catalyzed amination with BINAP as ligand, 149 although the findings are almost certainly applicable to biaryl phosphine ligands.…”
Section: Key Variablesmentioning
confidence: 99%
“…149 In this situation, the particle size and shape of the inorganic base can be important in determining the rate and ultimate success of a cross-coupling reaction. 150, 151 This topic has seen the most detailed discussion by Maes in the use of Cs 2 CO 3 in Pd-catalyzed amination with BINAP as ligand, 149 although the findings are almost certainly applicable to biaryl phosphine ligands. Cs 2 CO 3 from different suppliers exhibited varying reactivity and SEM imaging of the base showed a correlation between the particle properties and the activity of the base.…”
Section: Key Variablesmentioning
confidence: 99%
“…This feature may be attributed to the "base effect" hypothesis which suggests that liquid-solid interphase deprotonation of the palladium(ii)-amine complex is the rate-determining step. [32] It was found that using 1.2 equiv. benzophenone imine, 0.04 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of DMF by acetonitrile and lowering the temperature (85°C, 10 h) did not result in increased yield of IIIb. The amination of I using a different catalytic system, Pd(OAc) 2 /BINAP (2/8 mol %), and cesium carbonate as base (solvent toluene) [17] was characterized by considerably lower yield of the target product. Thus the most efficient were Pd(OAc) 2 /BINAP as catalytic system and triethylamine as base.…”
mentioning
confidence: 99%